2014
DOI: 10.1063/1.4900951
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size scaling law of the Néel temperature in hematite nanostructures

Abstract: Finite-size scaling relation of the Curie temperature in barium hexaferrite plateletsWe report high-temperature magnetic properties of single-crystalline hematite (a-Fe 2 O 3 ) nanostructures with different shapes. Magnetic measurements under a high vacuum (<9.5 Â 10 À6 Torr) up to 920 K were used to characterize thermal stability of the nanostructures. The onset temperature of the a-Fe 2 O 3 to Fe 3 O 4 phase transformation and the transformed fraction were found to depend strongly on the shape of the nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In the smallest particles, T C is found to be 221 of the scaling exponent with respect to particle shape can be seen. This consistency of results close to the accepted value of the scaling exponent contrasts with the range of values of ν found in other studies [9,10,12,15].…”
supporting
confidence: 60%
See 1 more Smart Citation
“…In the smallest particles, T C is found to be 221 of the scaling exponent with respect to particle shape can be seen. This consistency of results close to the accepted value of the scaling exponent contrasts with the range of values of ν found in other studies [9,10,12,15].…”
supporting
confidence: 60%
“…Studies of hematite and magnetite nanoparticles have found values for ν in the range of 0.6-0.8 [9,10], close to the 50 expected value of 0.7043 [11] for the 3D Heisenberg model. 51 A value of ν = 1.06 was determined from work conducted on 52 Ni nanoparticles [12], with line dislocations near the surface 53 of the nanoparticles suggested as the cause of this discrepancy.…”
Section: Introductionmentioning
confidence: 53%
“…In contrast to the latter strong effect on T M , finite size only weakly affects the second-order Néel transition. Recent high-T data on hematite nanostructures indicates that T N obeys the standard form ðT c =T 0 Þ ¼ 1 − ðL 0 =LÞ 1=ν governed by a typical suppression length L 0 ¼ 2.3 nm, and a scaling exponent near the Ising value ν ¼ 0.6 [38]. Applying the same form to the Morin transition, Fig.…”
mentioning
confidence: 79%
“…2b). From the outer diameters, thickness, and length histograms [20], the mean outer diameters, thickness, and length are found to be 148, 50, and 115 nm for the nanorings, respectively. The structural details of a-Fe 2 O 3 and a-Fe 2 O 3 @C nanorings are displayed in Fig.…”
Section: Electrochemical Measurementsmentioning
confidence: 98%